2018
DOI: 10.3347/kjp.2018.56.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cryptosporidium spp. in Diarrheic Immunocompetent Patients in Beni-Suef, Egypt: Insight into Epidemiology and Diagnosis

Abstract: Cryptosporidium species is an important cause of gastrointestinal infections globally. This study aimed to shed light on its role in diarrheic immunocompetent patients in Beni-Suef, Egypt and to compare three diagnostic methods. Two hundred diarrheic patients, 37±16.8 year old, were enrolled. Stool samples were examined by light microscopy, using modified Ziehl-Neelsen stain (MZN) for Cryptosporidium spp. oocysts. Coproantigens were detected by sandwich ELISA. DNA molecular diagnosis was done by nested PCR. PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a study of 200 patients with diarrhea, fecal samples were examined using microscopy (modified acid-fast staining), sandwich enzyme-linked immunosorbent assay (ELISA), and nested PCR. 21 Compared with ELISA and microscope, PCR has the highest detection rate (21%, 12.5% and 9.5% respectively). In this case, although the DNA sequence levels of C. parvum and C. hominis were similar (> 96%), we still found Cryptosporidium DNA in the blood of the patient via mNGS and identified its species, providing directions for subsequent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 200 patients with diarrhea, fecal samples were examined using microscopy (modified acid-fast staining), sandwich enzyme-linked immunosorbent assay (ELISA), and nested PCR. 21 Compared with ELISA and microscope, PCR has the highest detection rate (21%, 12.5% and 9.5% respectively). In this case, although the DNA sequence levels of C. parvum and C. hominis were similar (> 96%), we still found Cryptosporidium DNA in the blood of the patient via mNGS and identified its species, providing directions for subsequent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ELISA was the reference method and modified acid-fast staining had 50% sensitivity and 100% specificity 15 . Gawad et al 16 detected Cryptosporidium using asit fast staining, ELISA and nested PCR. As a result, the staining method had 100% specificity and 45.2% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium spp. causes chronic diarrhea in patients with immune deficiency and is generally not severe in people with normal immunity 16 . Symptoms of immune-compromised patients, are mainly nausea, vomiting, abdominal cramps, fever, and watery diarrhea 17,9 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gawad et al . [ 40 ] reported that molecular diagnosis of human cryptosporidiosis is habitually superior to enzyme-linked immunoabsorbent assay (ELISA) and direct microscopy after concentration. Thus, our study strongly recommends preceding concentration techniques before specific staining (MZN) and DNA extraction to prevent false negative cases.…”
Section: Discussionmentioning
confidence: 99%